The production of honey and pot-pollen from stingless bee Tetragonula clypearis and their contribution to increase the farmers income in West Lombok, Indonesia - Supeno, Bambang; Erwan, Erwan; Agussalim, Agussalim (2022)
Beekeeping in stingless bees is called meliponiculture and the products are produced consists of honey, pot-pollen, and propolis. However, in West Lombok, Indonesia there is lack of information about the contribution of honey and pot-pollen sold on the beekeepers or farmers income. Therefore, the aims of this study were to determine the production of honey and pot-pollen from the stingless bee Tetragonula clypearis and their contribution to increase the farmer’s income. In this study was used 112 colonies of stingless bee Tetragonula clypearis were moved from the bamboo hives to the box hives. All colonies were meliponiculture for about 8 months in the yard and rice field and harvested in two periods namely the first was after four months of meliponiculture and the second was four months after the first harvested. The recent findings showed that the production of honey in the yard was ranging 153.2 to 164.2 ml/hive/4 months and in the rice field was ranging 153.2 to 160.5 ml/hive/4 months. The production of pot-pollen in the yard was ranging 43.3 to 47.6 g/hive/4 months and in the rice field was ranging 43.5 to 44.1 g/hive/4 months. The total production of honey in the yard was 17,776 ml/8 months/56 colonies and in the rice field was 17,556 ml/8 months/56 colonies. The total production of pot-pollen in the yard was 5,093 g/8 months/56 colonies and in the rice field was 4,903 g/8 months/56 colonies. The contribution total of honey and pot-pollen on the farmers income in the yard was USD 503.791 and in the rice field was USD 496.032. It can be concluded that the yard and rice field can be used as the location for meliponiculture of stingless bee Tetragonula clypearis to increase the farmer's income based on the products of honey and pot-pollen. © 2022 Fundacion CIPAV. All rights reserved.